Arene ruthenium complexes as anticancer agents - Süss-Fink, Georg (My University, 2010)
Neutral or cationic arene ruthenium complexes providing both hydrophilic as well as hydrophobic properties due to the robustness of the ruthenium–arene unit hold a high potential for the development of metal-based anticancer drugs. Mononuclear arene ruthenium complexes containing P- or N-donor ligands or N,N-, N,O- or O,O-chelating ligands, dinuclear arene ruthenium systems with adjustable organic linkers, trinuclear arene ruthenium clusters containing an oxo cap, tetranuclear arene ruthenium porphyrin derivatives that are photoactive, as well as hexanuclear ruthenium cages that are either empty or filled with other molecules have been shown to be active against a variety of cancer cells.